Criteria followed in the establishment of a filamentous fungi culture collection - Micoteca da Universidade do Minho (MUM) - Santos, Isabel M. (2001)
In Portugal there are few culture collections of filamentous fungi and these are mostly in-house, and located mainly in the Lisbon area. Furthermore, open access to Portuguese databases on microorganisms is not well established. This knowledge and the continuing experimental activity in mycology, combined with an interest from the University in creating and financing reliable services to support research, led to the organization of a filamentous fungal culture collection, hosted at the Biological Engineering Centre of Minho University, in the North of Portugal. The Micoteca da Universidade do Minho (MUM), was established in 1996, with the aim of maintaining and providing strains for research on biotechnology and for use in teaching laboratories, and to act as a centre of expertise, information and training, complying with international quality standards. The use of a computerized system for the management of recorded data and the collection's holdings was envisaged from the start. The collection now holds 128 identified species, including recognized standard or test strains and isolates derived from research activities, mainly of the genera Penicillium and Aspergillus. The microbial strain database was built in-house and runs on Windows 2000. To ensure widespread availability of details of the collection's holdings, the fields intended for general searching and viewing are available on-line at http://www.micoteca.deb.uminho.pt/.